2010
DOI: 10.1089/fpd.2010.0611
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Assessment in Strawberry Production and Recommendations to Establish a Good Agricultural Practice System

Abstract: This study conducted microbiological assessment in tunnel style strawberry greenhouses and packaging centers and suggested recommendations to establish a good agricultural practice for strawberry production. The samples from irrigation water, workers' gloves, harvest bins, soil, strawberry leaves and strawberries in greenhouses, packers' gloves, conveyor belts, packaging tables, and door knobs of entrances in packaging centers were collected. Bacterial cell counts of aerobic plate counts, coliforms, Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…This method can extend the shelf life of strawberries without any negative impact on antioxidant activity, amounts of phenols and anthocyanins, or color. Yoon et al 15 suggest that food safety practices in strawberry greenhouses and packaging centers should be improved, and their suggestions may be useful in the establishment of a good agricultural practice system for strawberry production.…”
Section: Silva Srm Et Al -Detection Of Intestinal Parasites In Strawmentioning
confidence: 99%
“…This method can extend the shelf life of strawberries without any negative impact on antioxidant activity, amounts of phenols and anthocyanins, or color. Yoon et al 15 suggest that food safety practices in strawberry greenhouses and packaging centers should be improved, and their suggestions may be useful in the establishment of a good agricultural practice system for strawberry production.…”
Section: Silva Srm Et Al -Detection Of Intestinal Parasites In Strawmentioning
confidence: 99%
“…Nevertheless, fresh produce can serve as a vehicle for many food-borne pathogenic microorganisms [5]. The most frequent pathogenic bacteria isolated from the fresh products were usually Salmonella, Escherichia coli O157:H7, Listeria monocytogenes, and S. aureus, which could also survive in the fresh and frozen strawberries beyond the expected shelf life, causing severe human infection and death, consequently posing a particular health hazard to consumers [5][6][7][8][9][10]. Moreover, S. aureus is also considered as an important hazard due to producing staphylococcal enterotoxins, which could result in staphylococcal food poisoning (SFP) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey carried out by the US Food and Drug Administration (FDA), Salmonella was detected in one of a total of 143 samples of imported strawberries [7]. Only a few studies have been found in the literature regarding primary production of strawberries, and the results from these surveys also indicate low occurrence of fecal indicators and typical pathogens on strawberries [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%